Electrodeposition and Characterization of p and n Sulfide Semiconductors Composite Thin Film. Issue 12 (1st January 2016) - Berretti, E.; Cinotti, S.; Caporali, S.; Cioffi, N.; Giaccherini, A.; Benedetto, F. Di; Foresti, M. L.; Montegrossi, G.; Lavacchi, A.; Vizza, F.; Picca, R. A.; Innocenti, M.
Abstract : In this article is proposed a new preparation method for composite ultra-thin films for photovoltaic application. Compounds such as Kesterites (CZTS, ternary and quaternary copper and zinc sulfides) could be used in virtue of their semiconductor behavior in conjunction with electrodeposition from aqueous media methodologies; in particular E-ALD (Electrochemical Atomic Layer Deposition) method seems a legitimate alternative to the high pressure and temperature methods used since today. We studied the feasibility of the electrodeposition process of two layers of semiconductors (Cux Zny S, with p electronic proprieties, and CdS with n electronic proprieties), one above the other, by means of E-ALD. Preliminary electrochemical studies revealed the complex nature of the composite film, impairing the anodic stripping of Cd. In order to confirm that the Cd electrodeposition is surface limited, two sets of samples were compared using different conventional and charge controlled potentiostatic electrodeposition methodologies. SEM and XPS characterization was then performed to characterize morphologically and quantitatively the samples. Consequently, the conditions for the surface limited deposition of Cd over Cux Zny S have been reckoned through the electrochemical and spectroscopical analysis. The layered (p-n) structure of the thin film has been confirmed.